Leadership Training Policy Implementation at Inap Timor-Leste: Diagnosing Ineffectiveness and Strengthening Bureaucratic Capacity - Belarmino da Costa; Edy Sutrisno (Ilomata International Journal of Social Science, 2026)
Leadership training policy is a strategic instrument for developing the competency and professionalism of the civil service apparatus. In Timor-Leste, this mandate is institutionally assigned to the Instituto Nacional da Administração Pública (INAP) under Decree-Law No. 38/2012 and Decreto-Lei n.º 25/2016. Despite a legally sound normative foundation, implementation remains critically ineffective  evidenced by only 150 participants trained out of 3,527 officials holding structural positions over three years (2022–2024). This study investigates why legal clarity has not translated into effective implementation, employing a qualitative case study design with data drawn from semi-structured interviews, document analysis, and field observation involving ten purposively selected informants. Analysis is framed through the Van Meter and Van Horn model, which reveals that the implementation gap stems from six interconnected failures: unoperationalized policy standards in the curriculum, insufficient human and material resources, unsystematic inter-organizational communication, weak characteristics of implementing agents, volatile socio-political conditions, and inconsistent implementor disposition. The study's specific contribution lies in empirically diagnosing these causal linkages within a nascent post-independence state context, where bureaucratic capacity-building remains structurally constrained. Findings suggest that normative adequacy alone is insufficient; effective implementation requires operationalized standards, strengthened resource capacity, coordinated inter-agency mechanisms, and institutionalized commitment among implementing actors.